Reducing Avoidable Hospitalizations and Improving Quality in Nursing Homes With APRNs and Interdisciplinary Support: Lessons Learned. Issue 1 (January 2018) - Rantz, Marilyn J.; Popejoy, Lori; Vogelsmeier, Amy; Galambos, Colleen; Alexander, Greg; Flesner, Marcia; Murray, Cathy; Crecelius, Charles
Abstract : Supplemental Digital Content is Available in the Text.